POPULATION AWARENESS OF THE HARMFULNESS OF SOSNOWSKY’S HOGWEED IN REZEKNE MUNICIPALITY - Kotane, Inta; Zvaigzne, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Invasive alien species are one of the most urgent problems to be addressed to maintain biodiversity in the world. Sosnowsky's hogweed (Heracleum sosnowskyi) has been included in Latvia’s list of invasive alien species. The population’s awareness of the problem of Sosnowsky's hogweed may be viewed as one of the preventive measures to avoid the spread of the weed, which also allows optimally using financial resources. Research studies show that the levels of public awareness of Sosnowsky's hogweed and its harmfulness are different. The paper is based on the implementation results for the research grant "Investigation into the Information Society regarding the Control and Hazards of Sosnowsky's Hogweed in Rezekne Municipality”. The research aim of the paper is to examine the Rezekne municipality population’s awareness of the harmfulness of Sosnowsky's hogweed and their wish to acquire or build up their knowledge about the harmfulness of Sosnowsky's hogweed based on the results of a survey/interview of experts and a survey of the population. The research results – the results of the survey and the interview – revealed that the population could identify Sosnowsky's hogweed in nature, and the population, including agricultural land owners/managers were sufficiently informed about the harmfulness of Sosnowsky's hogweed. For the population, the most appropriate way of acquiring information about Sosnowsky's hogweed would be Internet websites, even though the experts considered the websites to be a partly effective way of informing the public. Research methods used: monographic, descriptive, analysis, synthesis, data grouping and sociological methods – a survey/interview of industry experts and a survey of the population.